2020
DOI: 10.1177/1471301220977710
|View full text |Cite
|
Sign up to set email alerts
|

What is the present role for general practitioners in dementia care? Experiences of general practitioners, patients and family carers in Portugal

Abstract: Background Governments are being challenged to integrate at least part of dementia care into primary care. However, little is known about the current role of general practitioners (GPs) regarding dementia care, especially in countries that do not have dementia strategies in place. The aim of this study was to explore the experiences of GPs, persons with dementia and their family carers in Portuguese primary care settings, to better understand GPs’ contribution to dementia care. Methods A qualitative interview … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 31 publications
2
15
0
1
Order By: Relevance
“…As in our previous studies (Balsinha et al, 2021), four groups of primary care centres within the Lisbon metropolitan area were selected to reflect different socio-economic characteristics.…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…As in our previous studies (Balsinha et al, 2021), four groups of primary care centres within the Lisbon metropolitan area were selected to reflect different socio-economic characteristics.…”
Section: Settingmentioning
confidence: 99%
“…In an earlier publications (Balsinha et al, 2021), we explored the role of GPs in dementia care in Portugal and found that GPs contributed little, working alone despite being members of multidisciplinary teams. The provision of dementia care by PNs has been explored in the literature; a recent systematic review identified its potential benefits (e.g., increased patient accessibility to PNs, early recognition and management of cognitive changes, better care management) as well as limitations (e.g., lack of definition of PN roles, inadequate dementia training, time constraints and poor communication with GPs) (Gibson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Since family physicians (FPs) act as gatekeepers of the care pathway, they should have the capacity to detect early cognitive decline, provide information and appropriate referral to specialists, and reduce the use of harmful or ineffective interventions (3). Despite the attention to a timely diagnosis, in Italy and other European countries dementia is underrecognized and under-managed in primary care settings (4)(5)(6), and cognitive decline is often not mentioned in the medical records until it is indicative of a serious condition (7). A previous experience from a study (the REMIND study) in the Health Authority (HA) of Milan in Northern Italy revealed difficulties in the ability of FPs to early recognize cognitive decline and provide appropriate referral to a specialized service.…”
Section: Introductionmentioning
confidence: 99%
“…In our face-to-face interviews, 3 the family doctors expressed empathy about caregivers' burden and provided unstructured emotional support, but few considered caregivers to be their primary focus of attention. Their ability to make even minimal assessment of caregivers' needs depended on the patient and caregiver consulting the same family doctor.…”
mentioning
confidence: 99%